Utilization of workflow management system for virtual machine instance management on cloud. (24th July 2015) - Kim, Huioon; Chun, Kyungwon; Kim, Hyounggyu; Chung, Youngjoo
Summary: The concept of virtualization is one of the most important technologies to construct a cloud service, and especially hardware virtualization is indispensable for infrastructure as a service (IaaS) where the cloud offering, infrastructure, is usually provided as a pool of virtual machine (VM) instances. For that reason, many public IaaS clouds like Amazon Web Service and private cloud toolkits such as Eucalyptus and OpenStack provide users with methods for managing VM instances via APIs, command‐line tools, web services, and so on. These are, however, not easy to use or customize for the average end users, especially for those in scientific research areas who just want to perform their work on a cloud and do not need to know the underlying technologies that much. Utilizing workflow management systems (WfMSs) in managing VMs on a cloud can alleviate these difficulties. Users only need to describe parameters needed for VMs and enact the workflow on a workflow enactment engine using user‐friendly interfaces. We propose a management scheme for VM instances on a cloud with the WfMS in this paper. We present a preliminary study on integrating cloud and WfMS focusing on management of VM instances and show an early implementation for a proof of concept with detailed explanations and possible usage scenarios. Copyright © 2015 John Wiley & Sons, Ltd.